Cuidados de enfermería humanizados dirigido a los neonatos - Uyaguari Sisalima, Flor Valeria (2025)
The Nursing Care Process is essential during a patient's stay in a healthcare unit, as the rapid recovery largely depends on the quality of care provided. For this reason, the study focuses on humanized nursing care directed at neonates, as these are a prioritized age group that depend entirely on the quality of nursing care received. Based on these considerations, the objective of this study is to identify the benefits of humanized nursing care for neonates. To achieve this, a bibliographic review was conducted, using sources from published scientific documents, academic journals, and peer-reviewed publications. The results of this research show that nursing, in its essence, is losing its fundamental role in direct patient care due to a shortage of professionals to meet demand and governmental requirements. Among the benefits for neonates, certain methodologies have been identified to help humanize nursing care for newborns, including parental and family involvement, early bonding with the mother, skin-to-skin contact, exclusive breastfeeding, open-door neonatal intensive care units (NICU) following ESAMYN regulations, and NIDCAP protocols. In conclusion, these methods contribute to improving the neurological, motor, and sensory development of newborns, thus preventing future complications.